Morphology and Molecular Phylogeny Reveal Five New Species of Laccaria (Hydnangiaceae, Agaricales) from Southern China - Ming Zhang; Xue-Lian Gao; Li-Qin Mu; Wang-Qiu Deng (Journal of Fungi, 2023)
The genus Laccaria is a type of cosmopolitan and ecologically important fungal group. Members can form ectomycorrhizal associations with numerous trees, and some species are common edible fungi in local markets. Although some new species from China are recently published, the species diversity of Laccaria is still unclear in China. In this study, some samples of Laccaria were collected from southern China, and morphological characteristics and phylogenetic analyses based on the multilocus dataset of ITS-LSU-tef1-rpb2 confirmed five new species. Laccaria miniata, L. nanlingensis and L. neovinaceoavellanea were collected from subtropical broad-leaved forests, and L. rufobrunnea and L. umbilicata were collected from subtropical mixed forests of southwest China. Full descriptions, illustrations, comparisons with similar species and phylogenetic analysis are provided.